Thermo-enzymatic hydrolysis of Cassava Starch by α-amylase and amyloglucosidase - Ku Syahidah, Ku Ismail; A.A. Ahmad; T. Inba; Khairul Farihan, Kasim; Mohamed Zulkali, Mohamed Daud (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 15th - 16th March 2008 at Putra Palace Hotel, Perlis.